2018
DOI: 10.1097/icu.0000000000000495
|View full text |Cite
|
Sign up to set email alerts
|

Comparing wavefront-optimized, wavefront-guided and topography-guided laser vision correction

Abstract: The data presented here should aid surgeons in understanding the effects of currently available LASIK treatment profiles. Surgeons should also be able to appreciate how the findings were used to create a decision tree to help choose the most appropriate treatment profile for patients. Finally, the retrospective evaluation of clinical outcomes based on the decision tree should provide surgeons with a realistic expectation for their own outcomes should they adopt such a decision tree in their own practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Many studies have compared the efficacy of WFO and WFG platforms for myopic correction and concluded that the two yield largely equivalent outcomes [4,17]. These studies are summarized in Table 4 [3][4][5][6][17][18][19][20][21][22][23][24]. FOZ has also been used as an effective tool for the assessment and comparison of different laser refractive surgery modalities [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have compared the efficacy of WFO and WFG platforms for myopic correction and concluded that the two yield largely equivalent outcomes [4,17]. These studies are summarized in Table 4 [3][4][5][6][17][18][19][20][21][22][23][24]. FOZ has also been used as an effective tool for the assessment and comparison of different laser refractive surgery modalities [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…6 Wavefront-optimized, wavefront-guided, and topographyguided treatments are ablation profiles available for LASIK and Trans-PRK, which could minimize the aberrations due to different principles. 67 Therefore, some articles showed similar, 62,68 or better, 66,69 aberrometric outcomes in wavefront-guided LASIK than in SMILE. When FS-LASIK was equipped with wavefrontguided ablation profiles, SMILE obtained more coma than FS-LASIK at 3-month, 69 6-month, 66 and 5-year 42 follow-up.…”
Section: Lasik Vs Smilementioning
confidence: 99%
“…Methods of correcting vision include corrective eyeglasses, hard and soft contact lenses, ortho-correction, laser vision correction (LVC), and refractive lens exchange [ 3 , 4 ]. Despite the numerous conservative treatment methods for vision defects, LVC procedures are becoming increasingly popular [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%